Pemeliharaan Website Kantor CV. Jiel Anugrah Adhitama Cipayung Jakarta Timur - Saputra Dwi Nurcahya; Sri Mardiyati; Dian Nazelliana; Purwanti Purwanti (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
This Community Service Program aims to improve the quality and sustainability of website management at CV. Jiel Anugrah Adhitama, located in Cipayung, East Jakarta. The main problems faced by the partner include outdated content, non-responsive website design, and low website security. The implementation methods included needs identification, technical planning, website maintenance, evaluation, and training for company staff. The results of the program showed significant improvements in website performance and security. Additionally, the company's internal staff demonstrated improved skills in independently managing and maintaining the website. This activity has had a positive impact in supporting digital transformation within the small and medium business environment.